PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENDEKATAN INKURI PADA MATERI MEKANISME TRANSPOR PADA MEMBRAN - Dwi Anugraheni Aily Fitriyah (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Abstract-This research is to develop learning device with inquiri approach in major the transport mechanism of membrane, describing the feasibility of learning device, the result of learning, and responses of the student in major of biology. This research is kind of the develop research use the development of Kemp’s model, to get inquiry learning which the oretically and empirically. The methods of this research is using a review of inquiry approach in learning. The result of this reseach want to get a validation of learning device with using inquiry appoarch in major the transport mechanism of membrane include syllabus, lesson plan, student book, student worksheet and test result of learning which to fasible for use, with the average of score eligibility is 75,34 %. Keywords: learning device, inquiry approach, the transport mechanism in the membrane